Cs2SnI6 perovskites nanostructures as excellent photocatalytic degradation of organic dye pollutants in water under visible light: Synthesis and characterization - Fatemeh Yousefzadeh; Mojgan Ghanbari; Elmuez A. Dawi; Masoud Salavati-Niasari (Arabian Journal of Chemistry, 2023)
Pollution of surface waters containing chemical dye combinations and/or biological materials can have adverse effects on human health and other organisms, even in small quantities. The photocatalytic oxidation procedure has been widely regarded as a commercially viable method of removing environmental pollutants. In recent research, Caesium-hexaiodostannate nanostructures (Cs2SnI6) were prepared through a co-precipitation approach and their photocatalytic performance was analyzed. A number of surfactants were examined for their influence on the structure, purity, and morphology of the sample. It was found in the SEM data that the presence of surfactants has a negative impact on the morphology, which may be due to the inability to remove surfactants by calcination at high temperatures. Photocatalytic activity of Cs2SnI6 catalysts was demonstrated over a variety of organic dyes, including methylene blue (MB), rhodamine b (RhB), methyl orange (MO), and methyl violet (MV). Upon exposure to visible light for 180 min, 5 ppm methylene blue showed the greatest degradation (84.0%). Cs2SnI6 nanostructures are being applied for the first time in photocatalytic applications. Due to their wide bandgap (1.7 eV) in the visible region, they may be a suitable candidate for water purification. Moreover, the results indicated that the efficiency of photocatalysis was affected by various parameters, including pH, dye concentration, dye types, catalyst dosages, and surfactants. In the recyclability test, Cs2SnI6 nanostructures were found to be stable, and the removal efficiency was reduced by 6.9% after the fifth run.